2011
DOI: 10.1007/s00383-011-3015-0
|View full text |Cite
|
Sign up to set email alerts
|

Paediatric sutureless circumcision—an alternative to the standard technique

Abstract: The use of 2-OCA as a tissue adhesive for sutureless circumcisions is an alternative to the standard suture technique. The use of this tissue adhesive, 2-OCA, results in comparable complication rates to the standard circumcision technique and results in excellent post-operative cosmetic satisfaction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
13
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 18 publications
3
13
0
Order By: Relevance
“…[31] Decrease in the incidence of sinus formation, and tissue granulation is another important advantage of these adhesives. [32] The above-mentioned problems developing during circumcision using laser, have been overcomed by additional use of tissue adhesives. On the other hand they prevent the risk of development of hematoma, and suture-related adhesions.…”
Section: Urethra and Spongiosal Tissuementioning
confidence: 99%
See 1 more Smart Citation
“…[31] Decrease in the incidence of sinus formation, and tissue granulation is another important advantage of these adhesives. [32] The above-mentioned problems developing during circumcision using laser, have been overcomed by additional use of tissue adhesives. On the other hand they prevent the risk of development of hematoma, and suture-related adhesions.…”
Section: Urethra and Spongiosal Tissuementioning
confidence: 99%
“…On the other hand they prevent the risk of development of hematoma, and suture-related adhesions. [33] Kelly et al [32] used CA glues in 502 cases whom they performed suturless circumcision operations, and couldn't encounter postoperative complications as hematoma, and bleeding. Görgülü et al [33] used CA after circumcisions they performed using laser, and reported complications only at a minimum level.…”
Section: Urethra and Spongiosal Tissuementioning
confidence: 99%
“…15,16 In this study, the range of operative time between 3 and 10 minutes which is shorter than the traditional circumcision and then other technique of Sutureless circumcision. In 2005 Ozkan KU and Gonen M reported an average operative time 19.8 minutes with the use of tissue glue and 16 minutes with suturing and explain that the application of glue takes a longer time.…”
Section: Discussionmentioning
confidence: 80%
“…Rates of mild and moderate adverse events (bleeding, haematoma and infection) were not significantly different using the two methods and were comparable to those from other studies using open surgical techniques and tissue adhesive. [15] The main disadvantage that was encountered with the use of tissue adhesive was moderate (>2 cm) wound disruption that occurred in 1 (1%) participant at 2 days, 10 (10.1%) participants at 1 week and in 20 (20.8%) participants at 2 weeks. Wound separation generally occurred only after the adhesive sloughed at days 5 -10.…”
Section: Discussionmentioning
confidence: 99%